Konsep Thariqah al-Ta’sisiyyah al-Arabiyah - Sugirma Sugirma; Agustang K (Peneliti.net, 2020)
Arabic is a language that is very important in the world of education, especially Islamic education. Therefore, it is proper for this Arabic language to get great attention from all circles to be studied and taught with various motives for different purposes. Included among them is the great attention shown by Azhar Arsyad, by constantly developing Arabic learning in Madrasas and universities. In terms of learning methods, Azhar Arsyad often said that if you want to teach language, both Arabic and English should be strengthened by deepening the basic vocabulary around us. However we explain Qawaid, but it is not based on increasing vocabulary, so it is possible that learning will fail. This also led to a new method known as the Thariqah al-Ta'sisiyyah al-Arabiyyah. The formulation of the problem in this essay is how the position and existence of Arabic as an international language and what Azhar Arsyad's main thoughts are in learning Arabic. To study this, the researcher tried to find information through searching the relevant literature with the Thariqah al-Ta'sisiyyah al-Arabiyyah as the subject of his study. Keyword: Arabic, Learning, Ta'sisiyah